FAKTOR PENENTU NIAT PENGGUNAAN ULANG LAYANAN BANK DIGITAL DI INDONESIA - Pang, Peggy; Sitio, Rike Penta; Kurnia, Pepey Riawati (Among Makarti, 2024)
Abstract : This study aims to test the UTAUT2 model by examining the mediating role of intention to reuse on use behaviour in the context of digital banking services in Indonesia. The trust factor is included because trust influences positive behaviour in technology acceptance. A quantitative approach was utilized, with the sample consisting of digital banking users in Indonesia. Data collection was conducted through the distribution of questionnaires, resulting in a total sample of 346 respondents. The collected data was analyzed using the bootstrapping technique with SEM-PLS (SmartPLS 4.0). The results indicate a significant influence of intention to reuse on use behaviour. Additionally, this  study identifies a relationship between performance expectancy and intention to reuse, as well as between habit and use behaviour. However, effort expectancy, social influence, hedonic motivation, price value, facilitating conditions, habit, and trust were found to have no significant effect on intention to reuse. Achieving performance expectancy is shown to have a positive impact on the intention to reuse digital banking services.Abstrak : Penelitian ini bertujuan untuk menguji model UTAUT2 dengan peran mediasi intention to reuse terhadap use behaviour pada penggunaan layanan bank digital di Indonesia. Faktor trust diikutsertakan karena trust mendefinisikan perilaku positif dalam penerimaan teknologi. Penelitian ini menggunakan pendekatan kuantitatif dengan sampel penelitian, yaitu pengguna layanan bank digital di Indonesia. Pengumpulan data dilakukan dengan penyebaran kuesioner yang total sampelnya berjumlah sebanyak 346 responden. Kemudian, data yang dikumpulkan dianalisis menggunakan teknik bootstrapping dengan bantuan aplikasi SEM-PLS (SmartPLS 4.0). Hasilnya adalah terdapat pengaruh antara intention to reuse terhadap use behaviour. Penelitian ini juga terdapat hubungan antara performance expectancy terhadap intention to reuse dan habit terhadap use behaviour. Namun, effort expectancy, social influence, hedonic motivation, price value, facilitating conditions, habit, dan trust tidak berpengaruh terhadap intention to reuse. Penelitian ini menunjukkan ketika performance expectancy tercapai maka akan berpengaruh positif terhadap penggunaan kembali layanan bank digital.